Detailed characterization and kinetic modeling of hemicellulose pyrolysis: A new approach for biomass in the CRECK-S-B framework - Muhammad Yusuf Suleiman; Eleonora Benedetto; Veronica Piazza; Leon Loni Berkel; Nicholas Musyoka; Wai Siong Chai; Christian Hasse; Luca Lietti; Alessandra Beretta; Alessio Frassoldati; Tiziano Faravelli; Paulo Debiagi (Fuel, 2026)

Phytoremediation performance of various tropical plant species for environmental remediation of high 137Cs contaminated soils: A case study of Batan Indah soil - Gustri Nurliati; Nail Huga Dhiaulhaq; Rifdah Indriani Susanto; Tazkiya Syahidha; Vivia Karen; Maulana Asgaf; Alfiansyah Malik Nugroho; Gregorius Donny Setiawan; Susetyo Hario Putero; Nunung Prabaningrum; Widya Rosita; Agus Budhie Wijatna; et al. (Chemosphere, 2026)

Temporal dynamics of innate immune gene expression in teleost fish: A phase-based framework from inflammatory activation to regulatory homeostasis - Munif Fadhilah; Mohammad Nurhafid; Satrio Ramadhani Budiarto; Muhammad Yusuf Hamka Utama (Veterinary Immunology and Immunopathology, 2026)

Geochemistry and sedimentology of cretaceous oceanic red beds (CORBs) of the Turonian Goru Formation (Sulaiman Range, Pakistan) - Ahmed Nur Dalmar; Shuja Ullah; Muhammad Hanif; Mahnoor Sabba; Abdalle Dahir Yusuf; Muhammad Rizwan (Journal of African Earth Sciences, 2026)

Dry reforming of methane on supported nickel catalysts: Recent advances on process modelling, carbon pathways and life cycle assessment - Ahmad Muhammad ABISO; Michalis A. VASILIADES; Xiaoyang WEI; Xiaolei FAN; Nicholas M. MUSYOKA; Abdulazeez Yusuf ATTA; Antonis A. ZORPAS; Angelos M. EFSTATHIOU; Paulo DEBIAGI (Chemical Engineering Journal, 2026)

Unveiling Breeding Tools for Improving Fruit Set in Oil Palm through Biotechnological Approaches: A Systematic Review - Gigih Ibnu Prayoga; Nono Carsono; Farida Damayanti; Muhammad Yusuf (Plant Molecular Biology Reporter, 2026)

Retraction notice to “Effects of dumpsite leachate plumes on surface and groundwater and the possible public health risks” [Sci. Total Environ. 897 (2023) 165469] - Joseph Omeiza Alao; Abubakar Fahad; Hazem Ghassan Abdo; Daniel A. Ayejoto; Hussin Almohamad; Muhammad Sani Ahmad; Mohammed Shettima Nur; Theophilus Toro Danjuma; Mumeen Adebayo Yusuf; Olaleye Timilehin Francis; Alao Ovaioza Joy (Science of The Total Environment, 2026)

Chemical features consistently associated with kinase inhibitor activity: a cross-target SHAP analysis under scaffold-split evaluation - Abubakar Siddiq Salihu; Muhammad Sulaiman Rahama; Wan Mohd Nuzul Hakimi Wan Salleh; Nura Suleiman Gwaram; Ahmed Salisu; Sulaiman Sani Yusuf (Molecular Diversity, 2026)

Spatial–multivariate modelling of seagrass ecological quality index (SEQI) in Central to Eastern Indonesia - Rohani Ambo-Rappe; Muhlis Muhlis; Muhammad Banda Selamat; Yayu A. La Nafie; Supriadi Mashoreng; St. Firjatih Widhah; Suci Rahmadani Artika; Hendriyadi Bahtiar Daeng Sila; Arini E. Lestari; Khairul Amri; Mahatma Lanuru; Fegi Nurhabni; et al. (Science of The Total Environment, 2026)

Provenance, tectonic settings, depositional conditions, and diagenetic features of the late Cretaceous (Coniacian–Santonian) Fika Shale, Upper Benue Trough, Northeastern Nigeria: Implications for hydrocarbon potential - Abdulwahab Bello; Musa B. Usman; Shehu Mukkafa; Ibrahim A. Kwami; Usman Abubakar; Abduljamiu O. Amao; Anas M. Salisu; Khalid Al-Ramadan; Muhammad A. Ismail; Abubakar S. Maigari; Ahmed I. Haruna; Bandar D. Al-Otaibi; et al. (Journal of African Earth Sciences, 2026)

Tailoring subcritical water extraction conditions to enhance antioxidant selectivity from kale (Brassica oleracea var. acephala) - Nurul Faezawaty Jamaludin; Rosnah Shamsudin; Muhammad Hazwan Hamzah; Mohd Zuhair Mohd Nor; Muhamad Yusuf Hasan; Jaturapatr Varith (Innovative Food Science & Emerging Technologies, 2026)

Dual-template structure-based design of novel harmine derivatives as EGFR inhibitors for colorectal cancer therapy - Sagir Yusuf Ismail; Murtala Muhammad; Tasiu Abdulmumin Mikail; Zakari Nuhu Lambu; Bishir Usman (In Silico Pharmacology, 2026)

Two decades of coral monitoring reveal thermal stress thresholds on Indonesian reefs - Tries B. Razak; Cut Aja Gita Alisa; Muhammad Abrar; Rizya Ardiwijaya; Imam Bachtiar; Ravienkha R. Budaya; Dan Exton; Giyanto; Aradea R. Hakim; Muhammad Erdi Lazuardi; M. Munasik; Efin Muttaqin; et al. (Biological Conservation, 2026)

Analyzing Spatial Urban Features Correlating with Night-Time Light Emission - Lala Septem Riza; Fajar Zuliansyah Trihutama; Muhammad Fajar Yusuf Firdaus; Zulfikar Ali Yunara Putra; Judhistira Aria Utama; Khyrina Airin Fariza Abu Samah; Dhani Herdiwijaya; Rinto Anugraha NQZ; Emanuel Sungging Mumpuni (Journal of the Indian Society of Remote Sensing, 2026)

SARS-CoV-2 antibody responses during the omicron wave in kano, nigeria: Implications for strengthening future vaccine strategies - Bilkisu Ahmed; Jamilu Abubakar Bala; Taysir Ramadan Hafiz; Isah Abubakar Aliyu; Abdulhadi Sale Kumurya; Ibrahim Muhammad Badamasi; Hayatu Saidu; Muhammad Adamu Abbas; Auwal Idris Kabuga; Alhassan Sharif Abdullahi; Bashiru Garba; Al-Mukhtar Yahuza Adamu; et al. (Next Research, 2026)

Fermentation of Robusta and Arabica coffee pulp using Leuconostoc mesenteroides: Antioxidant activity, chemical profiling, and anti-inflammatory potency - Amna Mohammed Marie; Marselina Irasonia Tan; Muhammad Yusuf Abduh (Food and Humanity, 2026)

Amine-appended bimetallic MOF-74 for highly selective and energy-efficient CO₂ capture under vacuum swing adsorption - Rodynah A. Alabdulhadi; Shabnam Khan; Md Delowar Hossain; Aamir Hanif; Mohammed Ahmed Sanhoob; Mohd Yusuf Khan; Mosim Ansari; Aasif Khan; Muhammad Usman; Saleh AlMansour; Aasif Helal (Chemical Engineering Journal, 2026)

The investigation of variations in chlorophyll-a in the southern coast of Sulawesi: a case study from 1998 to 2023 - Yusuf Jati Wijaya; Ulung Jantama Wisha; Bayu Munandar; Lilik Maslukah; Seto Windarto; Muhammad Zainuri (Remote Sensing Applications: Society and Environment, 2026)

Biomass pyrolysis kinetics considering lignin-hemicellulose interaction - Leon Loni Berkel; Paulo Debiagi; Hendrik Nicolai; Francesca Cerciello; Muhammad Yusuf Suleiman; Osvalda Senneca; Christian Hasse; Tiziano Faravelli (Fuel, 2026)

Synergistic integration of amorphous trimetallic phosphates with porous plate-like architecture for high-performance hybrid supercapacitors - Istiqomah; Ni Luh Wulan Septiani; Angga Hermawan; Muhammad Iqbal; Ahmad Nuruddin; Silvia Chowdhury; Nugraha; Yusuke Yamauchi; Yusuf Valentino Kaneti; Brian Yuliarto (Chemical Engineering Journal, 2026)

Integrated hydrogeochemical and multivariate statistical assessment of groundwater in Gashua, northeastern Nigeria: implications for arid zone aquifer management - Abdussalam Muhammad Auwal; Martins Uchenna Obidiegwu; Mohammed Yerima Kwaya; Ogechukwu Anastasia Ben-Owope; Josephmartin Izuchukwu Korie; Abdurrasheed Yusuf Muhammad; Musaab A. A. Mohammed; Tamás Madarász (Modeling Earth Systems and Environment, 2026)
Groundwater is the primary source of potable and irrigation water in Gashua, Northeastern Nigeria, where arid climatic conditions limit surface water availability. Unlike previous studies in the Chad Basin that focused on limited chemical parameters, this study applies integrated geospatial modelling and multivariate statistics to delineate hydrochemical facies and anthropogenic hotspots in a semi-arid aquifer. Twenty-five groundwater samples were analyzed for pH, electrical conductivity, total dissolved solids, total hardness, major cations (Ca²⁺, Mg²⁺, Na⁺, K⁺), and anions (Cl⁻, SO₄²⁻, NO₃⁻, HCO₃⁻). Results showed pH values from 5.7 to 7.9, EC between 415 and 1464 µS/cm, and TDS from 265.6 to 937.0 mg/L. 80% (20/25) of the samples exceeded the Nigerian Standard for Drinking Water Quality (NSDWQ) limit for hardness. Piper and Durov diagrams revealed Ca²⁺–Mg²⁺–Cl⁻–SO₄²⁻ and Ca²⁺–Mg²⁺–HCO₃⁻ facies, reflecting carbonate and sulphate dissolution, cation exchange, and evaporative concentration. Spatial analysis delineated recharge zones in the north and discharge zones in the south, with higher salinity and nitrate levels in peri-urban areas. Nitrate ranged from 10.8 to 88 mg/L, with one sample exceeding the World Health Organization (WHO) limit of 50 mg/L; sampling was conducted during the dry season. Principal Component Analysis (PCA) explained 79% of total variance and identified mineralization, pH buffering, and nitrate pollution as key processes. Hierarchical Cluster Analysis (HCA) classified wells into recharge, transitional, and discharge zones. Irrigation suitability assessed by SAR, Na⁺%, PI, KR, and MH confirmed that most samples are suitable, though moderate salinity (C2S1) and isolated sodicity risks highlight the need for site-specific management. These findings emphasize the vulnerability of groundwater to both natural geochemical evolution and human activities. The integrated hydrogeochemical and multivariate approach provides actionable implications: protecting recharge areas in the north, routine surveillance of southern salinity and nitrate hotspots, and tailored farmer advisories for irrigation practices. Such measures are critical for sustainable aquifer management in arid regions.

Whole-genome characterization and functional–structural analysis of GST variants in Orang Asli with comparative insights from Malays - Aishah Farliani Shirat; Muhammad Yusuf Abdul Zaid; Nurul Azmir Amir Hashim; Nurul Huda Mohamad Ikbal; Mohd Nur Fakhruzzaman Noorizhab; Eng Keng Seow; Mohammad Masrin Md Zahrin; Thane Moze Darumalinggam; Muhammad Danish Badrul Hisham; Teh Lay Kek; Mohd Zaki Salleh (In Silico Pharmacology, 2026)

Provenance, diagenesis and reservoir quality of the Aptian-Albian Bima sandstone, Upper Benue Trough, NE Nigeria - Yusuf Abdullahi Abdulkarim; Abdulwahab Muhammad Bello; Khalid Al-Ramadan (Journal of African Earth Sciences, 2026)

Unveiling deep-sea fish communities through eDNA analysis during extreme upwelling events in Pantar Strait, Indonesia - Yulita Dwi Astuti; Nining Nursalim; Muhammad Danie Al Malik; Ekitia Reyza Syakal; Lilik Maslukah; Yusuf Jati Wijaya; Rizki Taqwa Putranto; Heru Nur Krisna; Ikhsan Mustaqim; Azza Fidyani Sintania Susanti; R. Dwi Susanto; Ni Kadek Dita Cahyani; et al. (Regional Studies in Marine Science, 2025)

Effects of coffee pulp fermentation on bioactive compounds and antioxidant activity of coffee pulp extract: a systematic review and meta-analysis - Anasya Rahmawati; Muhamad Aldi Nurdiansyah; Intan Taufik; Mia Rosmiati; Rizki Fauziah Ramadhaini; Muhammad Yusuf Abduh (Food Bioscience, 2025)

Evaluation of phenolic compounds, antioxidant activity, and sensory analysis of commercial cascara from different locations in Indonesia - Anasya Rahmawati; Diah Nofitasari; Mia Rosmiati; Intan Taufik; Muhammad Yusuf Abduh (Food and Humanity, 2025)

Recirculating aquaculture systems: Advances, impacts, and integrated pathways for sustainable growth - Zubair Hashmi; Faizah Metali; Muhamad Amin; Muhammad Saifullah Abu Bakar; Yusuf Wibisono; Wahyunanto Agung Nugroho; Muhammad Roil Bilad (Bioresource Technology Reports, 2025)

Enhanced stability and coke resistance in methanol to olefins reaction using fibrous silica-wrapped silicoaluminophosphate zeolite - Muhammad Hafizuddin Mohd Sofi; Muhamed Yusuf Shahul Hamid; Aishah Abdul Jalil; Tuan Amran Tuan Abdullah; Mohamed Yusuf Mohamud; Mahadi Bahari; Nurul Sahida Hassan; Dai-Viet N. Vo (Environmental Chemistry Letters, 2025)

Sustainable integration of aquaculture wastewater treatment using Chlorococcum sp. in photobioreactor systems: Evaluation of nutrient removal, biomass productivity, and operational performance - Zubair Hashmi; Ibrahim Maina Idriss; Rieza Zulrian Aldio; Nur Aqidah Donglah; Juliana Zaini; Yusuf Wibisono; Muhammad Roil Bilad (Algal Research, 2025)

Advancement in hydrogen production, application and strategy towards sustainable energy: Malaysian case study - Mariam Ameen; Huei Yeong Lim; Haswin Kaur; Nur’aini Raman Yusuf; David Onoja Patrick; Muhammad Shahbaz; Abrar Inayat; Suzana Yusup (Process Safety and Environmental Protection, 2025)

An Analysis of the Fluctuation in Chlorophyll-a Concentration in the Sulu Sea During a 25-Year Period - Yusuf Jati Wijaya; Ulung Jantama Wisha; Lilik Maslukah; Imma Redha Nugraheni; Seto Windarto; Bayu Munandar; Muhammad Zainuri (Pure and Applied Geophysics, 2025)

Conservation for production? The benefits of mangroves for sustainable shrimp aquaculture - Aji W. Anggoro; Miguel Castro; Muhammad Ilman; Sara Leavitt; Basir; Mariski Nirwan; Vabian Adriano; Andi Trisnawati; Topik Hidayat; Rahmadi Muis; Dzimar A. R. Prakoso; Yusuf Fajariyanto; et al. (Aquaculture International, 2025)

First report of Schistocerca gregaria oil fractions against multidrug-resistant Pseudomonas aeruginosa clinical isolates - Tariq Mohammed Abdulazeez; Abdullateef Yusuf; John Sow Gudzan; Hussaini Ibrahim Mohammed; Muhammad Tukur Ibrahim; Helena Fodeke; Norashiqin Misni (Natural Product Research, 2025)

Green technology for radioactive waste treatment: Bio membrane perspective - Muhammad Yusuf; Shehzada Muhammad Sajid Jillani; Farid Fadhillah; Pieter David Boom; Isam H. Aljundi; Afaque Shams (Chemosphere, 2025)

Genome-wide identification of LOX gene in four cotton species and revealed its function in callus induction and drought tolerance - Sani Muhammad Tajo; Zhaoe Pan; K.M. Yusuf; Salisu Bello Sadau; Guowei Lv; Shoupu He; Xiaoli Geng; Xiongming Du (Plant Gene, 2025)

Association between admission hyperglycemia and prognosis in patients with acute myocardial infarction complicated with cardiogenic shock (AMI-CS): a systematic review, meta-analysis, and meta-regression of cohort study - Dennis Ievan Hakim; Faqrizal Ria Qhabibi; Muhammad Yusuf; Andika Bachtiar Effendi; Indra Prasetya (Next Research, 2025)

Utilization of duckweed in phytomining of gold mine tailing and its potential to produce gold nanoparticle - Rizki Maulana Yusuf; Muhammad Alhas Finaldin; Wahyuni Eka Putri; Aurora Karina Chandra; Akmal Jihad; Yuliati Herbani; Awalina Satya; Evi Susanti; Hamim Hamim (Environmental Science and Pollution Research, 2025)

A critical review about phytoremediation of heavy metals and radionuclides: from mechanisms to post-remediation strategies - Zeni Anggraini; Gustri Nurliati; Hendra Adhi Pratama; Heru Sriwahyuni; Raden Sumarbagiono; Nazhira Shadrina; Mirawaty Mirawaty; Niken Siwi Pamungkas; Zico Pratama Putra; Muhammad Yusuf (Chemosphere, 2025)

Composite films based on chitosan incorporating molybdenum disulfide nanosheets and zinc oxide nanoparticles with potential antibacterial application - Muhammad Iqbal Hidayat; Andri Hardiansyah; Khoiriah Khoiriah; Evi Yulianti; Riesca Ayu Kusuma Wardhani; Fahrialdi Fahrialdi; Muhammad Rayhan Izzati Yusuf (Food Chemistry, 2025)

Enhanced antifouling performance of cellulose acetate membranes via tannic acid–ferric ion coatings for microalgae harvesting - Afrillia Fahrina; Kajornsak Faungnawakij; Fahrurrozi Fahrurrozi; Apri I. Supii; Sri Mulyati; Nasrul Arahman; Yusuf Wibisono; Muhammad Roil Bilad (Bioresource Technology Reports, 2025)

Transfersome-based delivery of Muntingia calabura fruit extract for anti-aging applications - Syamsu Nur; Muhammad Fadly Noor Alwani; Fitriyanti Jumaetri Sami; Amriani Sapra; Andi Nur Aisyah; Maulita Indrisari; Nursamsiar; Nurul Arfiyanti Yusuf; Aristianti (Biocatalysis and Agricultural Biotechnology, 2025)

Dual-layer flat sheet membrane from waste cellulose acetate for natural organic matter removal from surface water - Ibrahima Maina Idriss; Zubair Hashmi; Norazanita Shamsuddin; Muhammad Saifullah Abu Bakar; Sutarat Thongratkaew; Kajornsak Faungnawakij; Yusuf Wibisono; Muhammad Roil Bilad (Journal of Water Process Engineering, 2025)

Optimization of ultrasonic-assisted extraction (UAE) for phenolics and antioxidant activity from cocoa (Theobroma cacao) leaves and phytochemical profiling using GC-MS and LC-HRMS - Yusuf Andriana; Muhammad Fatih Abdurrahman; Pepita Haryanti; Ratih Pangestuti; Dedy Kurnianto; Ardiba Rakhmi Sefrienda; Erni Apriyati; Jerry Wungkana; Ashri Indriati; Christina Litaay (Biocatalysis and Agricultural Biotechnology, 2025)

Mineral profiling of Turkish wheat genetic resources unveiled their conserved potential for biofortification in combating hidden hunger - Husnu Aktaş; Muhammad Azhar Nadeem; Yusuf Tutuş; Serap Doğan; Mehmet Karaman; İrfan Erdemci; Meng-Lu Wang; Jin-Ying Gou; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)

Recent advancements in nanocellulose reinforced biopolymer hybrid composites: A review - Abdul Habib; A.H.M. Firdaus; S.M. Sapuan; Hairul Abral; Muhammad Adlan Azka; E.S. Zainudin; A. Atiqah; J. Yusuf (Journal of Cleaner Production, 2025)

Linking provenance and diagenesis to reservoir quality evolution of sandstones: The Paleocene-Eocene Kerri-Kerri Formation, northeastern Nigeria - Abdulwahab M. Bello; Musa B. Usman; Abduljamiu O. Amao; Anas M. Salisu; Khalid Al-Ramadan; Usman Abubakar; Shehu Mukkafa; Ibrahim A. Kwami; Lukman U. Chiroma; Murtada Al-Hashem; Abubakar Yusuf; Abubakar S. Maigari; et al. (Marine and Petroleum Geology, 2025)

Mathematical analysis of chickenpox population dynamics unveiling the impact of booster in enhancing recovery of infected individuals - Kabiru Garba Ibrahim; James Andrawus; Abbas Abubakar; Abdullahi Yusuf; Stephen Ishaya Maiwa; Kefas Bitrus; Muhammad Sani; Ibrahim Abdullahi; Sunday Babuba; Joseph Jonathan (Modeling Earth Systems and Environment, 2025)

Synthesis of silk sericin/silk fibroin/Moringa oleifera-based hydrogel with antibacterial activity - Muhammad Iqbal Hidayat; Andri Hardiansyah; Riesca Ayu Kusuma Wardhani; Khoiriah Khoiriah; Evi Yulianti; Muhammad Rayhan Izzati Yusuf; Fahrialdi Fahrialdi (Biocatalysis and Agricultural Biotechnology, 2025)

Differentiation of Indonesian specialty cocoa (Theobroma cacao) varieties and origins using phenolic contents, antioxidant activities, and spectrometric fingerprints for traceability - Ariza Budi Tunjung Sari; Yusuf Andriana; Muhammad Fatih Abdurrahman; Dedy Kurnianto; Ardiba Rakhmi Sefrienda; Fitri Setiyoningrum; Des Saputro Wibowo; Truong Ngoc Minh (Food Bioscience, 2024)

Diagenesis and reservoir quality evolution of estuarine sandstones: Insights from the Cenomanian-Turonian Yolde Formation, northern Benue Trough, NE Nigeria - Abdulwahab M. Bello; Musa B. Usman; Abduljamiu O. Amao; Khalid Al-Ramadan; Murtada Al-Hashem; Aliyuda Kachalla; Usman Abubakar; Anas M. Salisu; Shehu Mukkafa; Ibrahim A. Kwami; Oluwafemi E. Aro; Muhammad Naveed Butt; et al. (Marine and Petroleum Geology, 2024)

Toll-like receptor expression in Pacific white shrimp (Litopenaeus vannamei) reveals differential responses after fungal (Fusarium solani) infection - Yusuf Jibril Habib; Chengjie Yao; Haifu Wan; Jiaming Lin; Hui Ge; Akram Ismael Shehata; Mayada Alhoshy; Muhammad Mohsin; Yilei Wang; Ziping Zhang (Aquaculture International, 2024)

Spatial variation, sources, and trajectory of black carbon in the South Sumatra Region of Indonesia using MERRA-2 reanalysis data - Muhammad Rendana; Novia Novia; Tuti Indah Sari; Maulana Yusuf; Idarwati (Acta Geophysica, 2024)

Zinc solubilizing bacteria synergize the effect of zinc sulfate on growth, yield and grain zinc content of rice (Oryza sativa) - Muhammad Shakeel; Fauzia Yusuf Hafeez; Imran Riaz Malik; Abdur Rauf; Farooq Jan; Ikramullah Khan; Iram Ijaz; Mohamed Farouk Elsadek; Muhammad Ajmal Ali; Kamran Rashid; Muhammad Muzammal; Muhammad Munir; et al. (Cereal Research Communications, 2024)
Zinc solubilizing bacteria inhabiting root endosphere possesses great potential to enhance plant yield by solubilizing the nutrients. The potential of Zn solubilizing bacteria Bacillus sp. SH-10 and Bacillus cereus SH-17 to improve yield and grain zinc content of rice was investigated under different regimes of individual and co-inoculation in the presence and absence of chemical fertilizer zinc sulfate (ZnSO 4 ). The strains were applied to the rice varieties basmati 385 and super basmati under field conditions for two consecutive years. A significantly improved growth of rice plants, such as plant height (102–118 cm), number of tillers per plant (8.5–11.5), chlorophyll content (29.5–35.1), zinc requiring enzymes, i.e., superoxide dismutase (396–570 per gram fresh weight (g −1 FW)), carbonic anhydrase activity (CA) (10–15.06 U g −1 FW) and grain yield (3.0–3.8 tons ha −1 ), was observed in the plants inoculated with Bacillus sp. in the presence of chemical fertilizer (ZnSO 4 ). Consortium of zinc solubilizing bacteria also caused higher grain Zn content (25.0–30.5 mg kg −1 ) of the rice varieties basmati 385 and super basmati as compared to that of un-inoculated plants. Hence, it can be concluded that Zn solubilizing bacteria has immense potential to be used as agricultural crop inoculants as they synergize the effect of chemical Zn, increase yield and improve the nutritional value of crops.

Neurotoxic snakebites in Africa: Clinical implications, therapeutic strategies, and antivenom efficacy - Abdulbaki Alfa-Ibrahim Adio; Ibrahim Malami; Nafiu Lawal; Amina Yusuf Jega; Bilyaminu Abubakar; Muhammad Bashir Bello; Kasimu Ghandi Ibrahim; Murtala Bello Abubakar; Abdussamad Abdussamad; Mustapha Umar Imam (Toxicon, 2024)

Seasonal variation of chlorophyll-a in South Java over the past quarter-century - Yusuf Jati Wijaya; Ulung Jantama Wisha; Lilik Maslukah; Seto Windarto; Anindya Wirasatriya; Muhammad Zainuri (Ocean Dynamics, 2024)

Soil nitrogen dynamics affected by coffee (coffea arabica) canopy and fertilizer management in coffee-based agroforestry - Syahrul Kurniawan; R Muhammad Yusuf Adi Pujo Nugroho; Reni Ustiatik; Istika Nita; Gabryna Auliya Nugroho; Cahyo Prayogo; Christopher W. N. Anderson (Agroforestry Systems, 2024)
Nutrient management in coffee-based agroforestry systems plays a critical role in soil nitrogen (N) cycling, but has not been well documented. The objective of this study was to evaluate the effect of coffee canopy management and fertilization on soil N dynamics. This study used a randomized complete block design (2 × 3 × 2) with four replications. There were three factors: 1) coffee canopy management (T1: Pruned, T2: Unpruned), 2) fertilizer type (O: Organic, I: Inorganic; M: 50% Organic + 50% Inorganic), and 3) fertilizer dose (D1: low, D2: medium, D3: high). Soil N dynamic indicators (i.e., total N, ammonium (NH 4 + ), nitrate (NO 3 − ), net N-NH 4 + , net N-NO 3 − , soil microbial biomass N) were measured at two soil sampling depths (0–20 cm and 20–40 cm). Results showed that pruning increased soil total N and microbial biomass N (MBN) by 10–56% relative to unpruned coffee trees. In contrast, the unpruned coffee canopy had 15–345% higher NH 4 + , NO 3 − , net N-NH 4 + , net N-NO 3 − , and microbial biomass N concentration than pruned coffee. Mixed fertilizer application increased NO 3 − and net N-NH 4 + accumulation by 5–15% relative to inorganic and organic fertilizers. In addition, medium to high dose fertilization led to a 19–86% higher net N-NO 3 − concentration and microbial biomass N as compared to low dose fertilization. The treatment of no pruning and mixed fertilizer at low to medium doses was the optimal management strategy to maintain soil available N, while pruning combined with organic fertilizer has the potential to improve soil total N and MBN.

Facile synthesis of novel zinc ferrite nanostructures (ZFN) for enhanced adsorption of highly mobile and toxic As(III) from aqueous solutions - Khurram Shehzad; Zhu Haifeng; Mukhtar Ahmad; Kareem Yusuf; Muhammad Tayyab Butt; Muniba Rahmat; Weihong Xu; Jinhuai Liu; Yuanguo Xu (Journal of Water Process Engineering, 2024)

Tailored design of CO2-selective mixed-matrix membranes using nitrile-functionalized COFs as 2D nanofillers - Bosirul Hoque; Mohd Yusuf Khan; Aamir Hanif; Mahmoud Abdelnaby; Aasif Helal; Abuzar Khan; Muhammad Usman; Qasem Ahmed Drmosh (Journal of Environmental Chemical Engineering, 2024)

Optimizing refuse-derived fuel production from scheduled wastes through Aspen plus simulation - Muhammad Afiq Zubir; Hesam Kamyab; Yasser Vasseghian; Haslenda Hashim; Ong Mei Zhi; Sameer Rajaratnam Abdullah; Mohammad Yusuf; Balasubramaniam Kapran; Afif Hamidi Kori; Noor Shawal Nasri; Hien Y Hoang (Environmental Research, 2024)

Multi-omics tools for understanding Trichoderma-plant symbiosis: biotechnological developments and future directions - Nur Syafikah Abdullah; Febri Doni; Muhammad Adil Awal; Muhamad Shakirin Mispan; Mohd Zuwairi Saiman; Yusmin Mohd-Yusuf; Nurul Shamsinah Mohd Suhaimi (Symbiosis, 2024)

Removal of cesium and strontium ions with enhanced solid-liquid separation by combined ion exchange and BaSO4 co-precipitation - Oguzhan Kivan; Muhammad Yusuf; David Harbottle; Timothy N. Hunter (Journal of Water Process Engineering, 2024)

Waste cellulose acetate-based dynamic membrane for NOM-containing river water filtration - Ibrahim Maina Idriss; Nurul Fadillah; Norazanita Shamsuddin; Muhammad Saifullah Abu Bakar; Sutarat Thongratkaew; Kajornsak Faungnawakij; Wahyunanto Agung Nugroho; Yusuf Wibisono; Asep Bayu Dani Nandiyanto; Muhammad Roil Bilad (Journal of Environmental Chemical Engineering, 2024)

Effective biological control of Lentil (Lens culinaris) Fusarium wilt and plant growth promotion through native Rhizobacteria - Javeria Ayub; Ayesha Tahir; Umer Iqbal; Huma Ayub; Muhammad Zeeshan Hyder; Amna Kiyani; Fauzia Yusuf Hafeez; Muhammad Kashif Ilyas; Abdul Ghafoor; Tayyaba Yasmin (Physiological and Molecular Plant Pathology, 2024)

Circular economy-based integrated farming system for indigenous chicken: Fostering food security and sustainability - Iffat Abbas Abbasi; Amjad Shamim; Muhammad Kashif Shad; Hasbullah Ashari; Ijaz Yusuf (Journal of Cleaner Production, 2024)

Kinetics and thermodynamic analysis of palm oil decanter cake and alum sludge combustion for bioenergy production - Kunmi Joshua Abioye; Noorfidza Yub Harun; Suriati Sufian; Mohammad Yusuf; Muhammad Irfan Khan; Ahmad Hussaini Jagaba; Surajudeen Sikiru; Sharjeel Waqas; Hesam Kamyab; Abdullah M. Al-Enizi; Satbir S. Sehgal; Manish Gupta; et al. (Sustainable Chemistry and Pharmacy, 2023)

RETRACTED: Effects of dumpsite leachate plumes on surface and groundwater and the possible public health risks - Joseph Omeiza Alao; Abubakar Fahad; Hazem Ghassan Abdo; Daniel A. Ayejoto; Hussin Almohamad; Muhammad Sani Ahmad; Mohammed Shettima Nur; Theophilus Toro Danjuma; Mumeen Adebayo Yusuf; Olaleye Timilehin Francis; Alao Ovaioza Joy (Science of The Total Environment, 2023)

Renewable hydrogen production via biological and thermochemical routes: Nanomaterials, economic analysis and challenges - Fazil Qureshi; Mohammad Yusuf; Muhammad Tahir; Moinul Haq; Montaha Mohamed Ibrahim Mohamed; Hesam Kamyab; Hong-Ha T. Nguyen; Dai-Viet N. Vo; Hussameldin Ibrahim (Process Safety and Environmental Protection, 2023)

Integrating of electrocoagulation process with submerged membrane bioreactor for wastewater treatment under low voltage gradients - Khalid Bani-Melhem; Maria Elektorowicz; Muhammad Tawalbeh; Abeer Al Bsoul; Ahmed El Gendy; Hesam Kamyab; Mohammad Yusuf (Chemosphere, 2023)

Natural resources revenues, shadow economy and financial institutions depth: The way forward - Faryal; Faisal Faisal; Muhammad Yusuf Amin; Zahoor Ul Haq; Sami Ur Rahman; Adnan Ali (Resources Policy, 2023)

Evaluating ionic liquids for its potential as eco-friendly solvents for naproxen removal from water sources using COSMO-RS: Computational and experimental validation - Huma Warsi Khan; Mohd Kaif Khan; Muhammad Moniruzzaman; Mohammed K. Al Mesfer; Mohd Danish; Kashif Irshad; Mohammad Yusuf; Hesam Kamyab; Shreshivadasan Chelliapan (Environmental Research, 2023)

Anti-Inflammatory, Antioxidant, Metabolic and Gut Microbiota Modulation Activities of Probiotic in Cardiac Remodeling Condition: Evidence from Systematic Study and Meta-Analysis of Randomized Controlled Trials - Nurpudji Astuti Taslim; Muhammad Yusuf; Ade Meidian Ambari; Imke Maria Del Rosario Puling; Filzatuz Zahro Ibrahim; Hardinsyah Hardinsyah; Rudy Kurniawan; William Ben Gunawan; Nelly Mayulu; Victor F. F. Joseph; Nindy Sabrina; Mochammad Rizal; et al. (Probiotics and Antimicrobial Proteins, 2023)
Heart failure (HF) is a global pandemic with increasing prevalence and mortality rates annually. Its main cause is myocardial infarction (MI), followed by rapid cardiac remodeling. Several clinical studies have shown that probiotics can improve the quality of life and reduce cardiovascular risk factors. This systematic review and meta-analysis aimed to investigate the effectiveness of probiotics in preventing HF caused by a MI according to a prospectively registered protocol (PROSPERO: CRD42023388870). Four independent evaluators independently extracted the data using predefined extraction forms and evaluated the eligibility and accuracy of the studies. A total of six studies consisting of 366 participants were included in the systematic review. Probiotics are not significant in intervening left ventricular ejection fraction (LVEF) and high-sensitivity C-reactive protein (hs-CRP) when compared between the intervention group and the control group due to inadequate studies supporting its efficacy. Among sarcopenia indexes, hand grip strength (HGS) showed robust correlations with the Wnt biomarkers ( p < 0.05), improved short physical performance battery (SPPB) scores were also strongly correlated with Dickkopf-related protein (Dkk)-3, followed by Dkk-1, and sterol regulatory element-binding protein 1 (SREBP-1) ( p < 0.05). The probiotic group showed improvement in total cholesterol ( p = 0.01) and uric acid ( p = 0.014) compared to the baseline. Finally, probiotic supplements may be an anti-inflammatory, antioxidant, metabolic, and intestinal microbiota modulator in cardiac remodeling conditions. Probiotics have great potential to attenuate cardiac remodeling in HF or post-MI patients while also enhancing the Wnt signaling pathway which can improve sarcopenia under such conditions.

MXenes and MXene-based materials for removal of pharmaceutical compounds from wastewater: Critical review - Muhammad Tawalbeh; Shima Mohammed; Amani Al-Othman; Mohammad Yusuf; M. Mofijur; Hesam Kamyab (Environmental Research, 2023)

Exploration of the bioenergy potential of Dactyloctenium aegyptium through pyrolysis, kinetics, and thermodynamic parameters to produce clean fuels and biochemicals - Hesham Alhumade; Omar S. Alayed; Muhammad Waqas Iqbal; Ayesha Shahid; Tanveer Iqbal; Muhammad Sajjad Ahmad; Ali Elkamel; Yusuf Al-Turki; Muhammad Aamer Mehmood; Ghulam Abbas Ashraf (Fuel, 2023)

An insight into the mechanisms of action of selected bioactive compounds against epigenetic targets of prostate cancer: implications on histones modifications - Babangida Sanusi Katsayal; Gilead Ebiegberi Forcados; Abdurrahman Pharmacy Yusuf; Yunus Aisha Lawal; Shehu Aisha Jibril; Hussaini Nuraddeen; Musa Mubarak Ibrahim; Idris Zubairu Sadiq; Murtala Bello Abubakar; Ibrahim Malami; Ibrahim Babangida Abubakar; Aliyu Muhammad (In Silico Pharmacology, 2023)

Weak base-modulated synthesis of bundle-like carbon superstructures from metal-organic framework for high-performance supercapacitors - Zu-Shun Fan; Yusuf Valentino Kaneti; Silvia Chowdhury; Xiohan Wang; Muhammad Rezaul Karim; Ibrahim Abdullah Alnaser; Fei-Bao Zhang (Chemical Engineering Journal, 2023)

Integrated hydrographic survey for proposed Jetty location along Benin River at Oghara Delta State, Nigeria - Stephen Olushola Oladosu; Alfred Sunday Alademomi; Tosin Julius Salami; Tijjani Yusuf Muhammad (Arabian Journal of Geosciences, 2023)

Plant-assisted synthesis and characterization of MnO2 nanoparticles for removal of crystal violet dye: an environmental remedial approach - Muniba Rahmat; Shumaila Kiran; Tahsin Gulzar; Mohd Yusuf; Rabia Nawaz; Javaira Khalid; Nooria Fatima; Ata Ullah; Muhammad Azam (Environmental Science and Pollution Research, 2023)

Quantifications and predictions of sectoral pollutants emissions in Nigeria from 1980 to 2050 - Khadijat Abdulkareem Abdulraheem; Jamiu Adetayo Adeniran; Adeniyi Saheed Aremu; Muhammad-Najeeb O. Yusuf; Rafiu Olasunkanmi Yusuf; Emmanuel Toluwalope Odediran; Jacob Ademola Sonibare; Mingxi Du (Environmental Monitoring and Assessment, 2023)

Effect of waste cooking oil on warm mix asphalt block pavement – A comprehensive review - Yusuf Babangida Attahiru; Azman Mohamed; Ahmed Eltwati; Aliyu Abubakar Burga; Abubakar Ibrahim; Abdullahi Muhammad Nabade (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Seasonal variability of Total Suspended Sediment off the Banjir Kanal Barat River, Semarang, Indonesia estimated from Sentinel-2 images - Anindya Wirasatriya; Lilik Maslukah; Elis Indrayanti; Muh. Yusuf; Adzkia Pincta Milenia; Alvin Aulia Adam; Muhammad Helmi (Regional Studies in Marine Science, 2023)

Efficacy of stem cell secretome in the treatment of traumatic brain injury: A systematic review and meta-analysis of preclinical studies - Suleiman Alhaji Muhammad; Abdullahi Yahya Abbas; Mustapha Umar Imam; Yusuf Saidu; Lawal Suleiman Bilbis (Molecular Neurobiology, 2022)

Insights to antimicrobial resistance: heavy metals can inhibit antibiotic resistance in bacteria isolated from wastewater - Massab Bashir Khaira; Muhammad Bilal Yusuf; Fariha Khan (Environmental Monitoring and Assessment, 2022)

Source identification and health risk assessments of heavy metals in indoor dusts of Ilorin, North central Nigeria - Maimuna O. Abdulraheem; Jamiu Adetayo Adeniran; Hafsat Abolore Ameen; Emmanuel Toluwalope Odediran; Muhammad-Najeeb O. Yusuf; Khadijat Abdulkareem Abdulraheem (Journal of Environmental Health Science and Engineering, 2022)

Source identification and health risk assessments of polycyclic aromatic hydrocarbons in settled dusts from different population density areas of Ilorin, Nigeria - Jamiu Adetayo Adeniran; Maimuna Orire Abdulraheem; Hafsat Abolore Ameen; Emmanuel Toluwalope Odediran; Muhammad-Najeeb O. Yusuf (Environmental Monitoring and Assessment, 2021)

Reduced root mycorrhizal colonization as affected by phosphorus fertilization is responsible for high cadmium accumulation in wheat - M. Atilla Yazici; Muhammad Asif; Yusuf Tutus; Ibrahim Ortas; Levent Ozturk; Hans Lambers; Ismail Cakmak (Plant and Soil, 2021)

Indoor transmission dynamics of expired SARS-CoV-2 virus in a model African hospital ward - Jamiu Adetayo Adeniran; Ishaq Alhassan Mohammed; Oladele Idris Muniru; Taofeek Oloyede; Omowonuola Olubukola Sonibare; Muhammad-Najeeb O. Yusuf; Khadijat Abdulkareem Abdulraheem; Emmanuel Tolulope Odediran; Rafiu Olasunkanmi Yusuf; Jacob Ademola Sonibare (Journal of Environmental Health Science and Engineering, 2021)

Annotation of AMP-activated protein kinase genes and its comparative transcriptional analysis between high and low lipid producing strains of Mucor circinelloides - Shaista Nosheen; Junhuan Yang; Tahira Naz; Yusuf Nazir; Muhammad Ijaz Ahmad; Abu Bakr Ahmad Fazili; Shaoqi Li; Kiren Mustafa; Yuanda Song (Biotechnology Letters, 2021)

Emission factors of some common grass species in West Africa - Khadijat Abdulkareem Abdulraheem; Jamiu Adetayo Adeniran; Adeniyi Saheed Aremu; Muhammad-Najeeb O. Yusuf; Jeleel Adekunle Adebisi; Nusirat Aderinsola Sadiku; Oluwatosin Onaopemipo Olofintoye; Abubakar Ismail; Jacob Ademola Sonibare (Environmental Monitoring and Assessment, 2020)

In silico predictions on the possible mechanism of action of selected bioactive compounds against breast cancer - Aliyu Muhammad; Babangida Sanusi Katsayal; Gilead Ebiegberi Forcados; Ibrahim Malami; Ibrahim Babangida Abubakar; Amina Isah kandi; Adam Muntaka Idris; Sabi’u Yusuf; Salihu Muktar Musa; Nagedu Monday; Zak-wan Sidi Umar (In Silico Pharmacology, 2020)

Utilization of Leucaena leucocephala and Gliricidia sepium as supplements by goats fed Panicum maximum basal diet - Muhammad Rusdy; Muhammad Yusuf; Ismartoyo (Tropical Animal Health and Production, 2020)

Effects of vitamin and mineral premix withdrawal from diets on carcass and meat quality of feedlot steers - Selma Büyükkılıç Beyzi; Yusuf Konca; Özlem Köknur; Sebahattin Köknur; Hasan Yalçın; Muhammad Jasim Uddin; Mehmet Ulaş Çınar (Tropical Animal Health and Production, 2019)

Pharmacological Manipulation of Trk, p75NTR, and NGF Balance Restores Memory Deficit in Global Ischemia/Reperfusion Model in Rats - Ali Mohamed Choucry; Muhammad Yusuf Al-Shorbagy; Ahmed Sherif Attia; Hanan Salah El-Abhar (Journal of Molecular Neuroscience, 2019)

Glucanolytic Rhizobacteria Produce Antifungal Metabolites and Elicit ROS Scavenging System in Sugarcane - Muhammad Atif Zia; Humaira Yasmin; Faluk Shair; Zahra Jabeen; Saqib Mumtaz; Zafar Hayat; Syed Zia ul Husnain Shah; Shahid Afghan; Fauzia Yusuf Hafeez; Muhammad Nadeem Hassan (Sugar Tech, 2019)

Homotypic Clusters of Transcription Factor Binding Sites in the First Large Intron of AGL24 MADS-Box Transcription Factor Are Recruited in the Enhancement of Floral Expression - Tajammul Hussain; Nazia Rehman; Safeena Inam; Wajya Ajmal; Amber Afroz; Aish Muhammad; Yusuf Zafar; Ghulam Muhammad Ali; Muhammad Ramzan Khan (Plant Molecular Biology Reporter, 2019)

Effect of predicted climate change on growth and yield performance of wheat under varied nitrogen and zinc supply - Muhammad Asif; Cevza Esin Tunc; Mustafa Atilla Yazici; Yusuf Tutus; Raheela Rehman; Abdul Rehman; Levent Ozturk (Plant and Soil, 2019)

Plant growth promoting rhizobacteria suppress blast disease caused by Pyricularia oryzae and increase grain yield of rice - Afroz Rais; Muhammad Shakeel; Fauzia Yusuf Hafeez; Muhammad Nadeem Hassan (BioControl, 2016)

Prediction of pore-water pressure response to rainfall using support vector regression - Nuraddeen Muhammad Babangida; Muhammad Raza Ul Mustafa; Khamaruzaman Wan Yusuf; Mohamed Hasnain Isa (Hydrogeology Journal, 2016)

The use of FAMACHA in estimation of gastrointestinal nematodes and total worm burden in Damara and Barbados Blackbelly cross sheep - Konto Mohammed; Yusuf Abba; Nur Syairah Binti Ramli; Murugaiyah Marimuthu; Mohammed Ariff Omar; Faez Firdaus Jesse Abdullah; Muhammad Abubakar Sadiq; Abdulnasir Tijjani; Eric Lim Teik Chung; Mohammed Azmi Mohammed Lila (Tropical Animal Health and Production, 2016)

Isolation and phylogenetic analysis of caprine Orf virus in Malaysia - Ashwaq Ahmed Abdullah; Muhammad Farid Bin Ismail; Krishnan Nair Balakrishnan; Jamilu Abubakar Bala; Homayoun Hani; Yusuf Abba; Mohd Kamaruddin Awang Isa; Faez Firdaus Jesse Abdullah; Siti Suri Arshad; Zeenatul Allaudin Nazariah; Rasedee Abdullah; Noordin Mohamed Mustapha; et al. (VirusDisease, 2015)

Suppression of red rot disease by Bacillus sp. based biopesticide formulated in non-sterilized sugarcane filter cake - Muhammad Nadeem Hassan; Namood-e-Sahar; Syed Zia-Ul-Husnain Shah; Shahid Afghan; Fauzia Yusuf Hafeez (BioControl, 2015)

Safe use of Cry genes in genetically modified crops - M. Rahman; Muhammad Zaman; Tayyaba Shaheen; Samra Irem; Yusuf Zafar (Environmental Chemistry Letters, 2015)

Fluoroquinolones: novel class of gastrointestinal dietary lipid digestion and absorption inhibitors - Yusuf M. Al-Hiari; Violet N. Kasabri; Ashok K. Shakya; Muhammad H. Alzweiri; Fatma U. Afifi; Yasser K. Bustanji; Ihab M. Al-Masri (Medicinal Chemistry Research, 2014)

Development of broad-spectrum insect-resistant tobacco by expression of synthetic cry1Ac and cry2Ab genes - Muhammad Nouman Sohail; Sohail Mehmood Karimi; Shaheen Asad; Shahid Mansoor; Yusuf Zafar; Zahid Mukhtar (Biotechnology Letters, 2012)

Erratum to: Engineering cotton (Gossypium hirsutum L.) for resistance to cotton leaf curl disease using viral truncated AC1 DNA sequences - Jamil A. Hashmi; Yusuf Zafar; Muhammad Arshad; Shahid Mansoor; Shaheen Asad (Virus Genes, 2011)

Molecular characterization of the modular chitin binding protein Cbp50 from Bacillus thuringiensis serovar konkukian - Muhammad Aamer Mehmood; Xiang Xiao; Fauzia Yusuf Hafeez; Yingbao Gai; Fengping Wang (Antonie van Leeuwenhoek, 2011)

Engineering cotton (Gossypium hirsutum L.) for resistance to cotton leaf curl disease using viral truncated AC1 DNA sequences - Jamil A. Hashmi; Yusuf Zafar; Muhammad Arshad; Shahid Mansoor; Shaheen Asad (Virus Genes, 2011)

Molecular characterization of an endochitinase from Bacillus thuringiensis subsp. konkukian - Muhammad Aamer Mehmood; Xiang Xiao; Fauzia Yusuf Hafeez; Yingbao Gai; Fengping Wang (World Journal of Microbiology and Biotechnology, 2010)

Erratum to: Suppression of red rot caused by Colletotrichum falcatum on sugarcane plants using plant growth-promoting rhizobacteria - Muhammad Nadeem Hassan; Shahid Afghan; Fauzia Yusuf Hafeez (BioControl, 2010)

Suppression of red rot caused by Colletotrichum falcatum on sugarcane plants using plant growth-promoting rhizobacteria - Muhammad Nadeem Hassan; Shahid Afghan; Fauzia Yusuf Hafeez (BioControl, 2010)

Codon optimization of cry1Ab gene for hyper expression in plant organelles - Rasheda Jabeen; Muhammad Sarwar Khan; Yusuf Zafar; Tehmina Anjum (Molecular Biology Reports, 2010)

Purification and characterization of a chitinase from Serratia proteamaculans - Muhammad Aamer Mehmood; Xiang Xiao; Fauzia Yusuf Hafeez; Yingbao Gai; Fengping Wang (World Journal of Microbiology and Biotechnology, 2009)

Studying the extent of genetic diversity among Gossypium arboreum L. genotypes/cultivars using DNA fingerprinting - Mehboob-ur-Rahman; Tahira Yasmin; Nabila Tabbasam; Ihsan Ullah; Muhammad Asif; Yusuf Zafar (Genetic Resources and Crop Evolution, 2008)

Relationship among acidophilic bacteria from diverse environments as determined by randomly amplified polymorphic DNA analysis (RAPD) - Tanveer Akbar; Kalsoom Akhtar; Muhammad A. Ghauri; Munir A. Anwar; Moazur Rehman; Mehboobur Rehman; Yusuf Zafar; Ahmad M. Khalid (World Journal of Microbiology and Biotechnology, 2005)

Assessment of genetic diversity among wheat (Triticum aestivum L.) cultivars from a range of localities across Pakistan using random amplified polymorphic DNA (RAPD) analysis - Muhammad Shahid Mukhtar; Mehboob-ur Rahmanw; Yusuf Zafar (Euphytica, 2002)